Improving Skin Cancer Treatment by Dual Drug Co-Encapsulation into Liposomal Systems-An Integrated Approach towards Anticancer Synergism and Targeted Delivery - Margarida Corte-Real; Francisco Veiga; Ana Cláudia Paiva-Santos; Patrícia C. Pires (MDPI AG, 2024)
Skin cancer is a high-incidence complex disease, representing a significant challenge to public health, with conventional treatments often having limited efficacy and severe side effects. Nanocarrier-based systems provide a controlled, targeted, and efficacious methodology for the delivery of therapeutic molecules, leading to enhanced therapeutic efficacy, the protection of active molecules from degradation, and reduced adverse effects. These features are even more relevant in dual-loaded nanosystems, with the encapsulated drug molecules leading to synergistic antitumor effects. This review examines the potential of improving the treatment of skin cancer through dual-loaded liposomal systems. The performed analysis focused on the characterization of the developed liposomal formulations' particle size, polydispersity index, zeta potential, encapsulation efficiency, drug release, and in vitro and/or in vivo therapeutic efficacy and safety. The combination of therapeutic agents such as doxorubicin, 5-fluorouracil, paclitaxel, cetuximab, celecoxib, curcumin, resveratrol, quercetin, bufalin, hispolon, ceramide, DNA, STAT3 siRNA, Bcl-xl siRNA, Aurora-A inhibitor XY-4, 1-Methyl-tryptophan, and cytosine-phosphate-guanosine anionic peptide led to increased and targeted anticancer effects, having relevant complementary effects as well, including antioxidant, anti-inflammatory, and immunomodulatory activities, all relevant in skin cancer pathophysiology. The substantial potential of co-loaded liposomal systems as highly promising for advancing skin cancer treatment is demonstrated.